RETAILER'S PREDICT CIGARETTE TAX INCREASE WOULD CREATE SERIOUS PROBLEMS FOR MASSACHUSETTS (Tufts Archival Research Center, 2007)
Massachusetts Package Stores Association, Inc article regarding negative impacts of a proposed cigarette tax increase in Massachusetts. Cites examples of negative impacts in Canada and in the U.S., mentioning cross border and illegal sales. Predicts increased sales to minors.